Generalized method of moments' characteristics and its application on paneldata - Utami, Bernadhita H. S; Warsono, Dian Kurniasari; Usman, Mustofa; Elfaki, Faiz Ahmed Mohamed (Sci.Int.(Lahore), 2014)
Generalized Method of Moments(GMM) is an estimation procedure that allows econometric models especially in panel data to be specified while avoiding often unwanted or unnecessary assumption, such as specifying a particular distribution for the errors, Panel data is combination of time series and cross section data that contain observations on thousands of individuals or families, each observed as several points in time. Furthermore, the Generalized Method of Moments estimator is obtained by minimizing the criterion function bu making sample moment match the population moment. The point of this research is to analyze characteristics GMM estimator on panel data fixed effect models especially unbiasedness, variance minimum, consistency, and normal asymptotic distributed estimator properties. This paper also provide the application of GMM estimation on the area of "Cost for United States Airlines on Six Firms from 1970-1984".